Exploring physical and phycological condition of Jahangirnagar University students residing near university area during COVID-19 pandemic - Salma, Nahid; Ahmed, Piyash; Rahman, Tareq; Alam, M. Asraful; Mahmud, Shohel (International Journal Of Community Medicine And Public Health, 2023)
Background: Due of the closure of all educational institute as well as lockdown, the pandemic has affected physical and psychological health of all level students specifically university level students. Although the online based education was started but that brought different challenge to them. Thus, the study aimed to explore the physical and psychological problems faced by Jahangirnagar University students who resides near university area. Methods: Data was collected through an online questionnaire (Google form) from Jahangirnagar University students who reside near the university area using convenient sampling method. To analyse the data, descriptive statistics, Chi-square test and ordinal logistic regression was executed along with graphical representations. Results: The study showed about 92.5% (moderately: 41.2 %, extremely severe: 18%, severe: 24.7%, mild: 8.6%) students were depressed while 94.8% extremely severe: 49.8%, mild: 2.2%, moderate: 15.4% and severe: 27.3%) students were suffering from anxiety problems during pandemic. Chi-square and ordinal logistic suggested “infected by COVID-19”, “sleeping time”, and “time usually spent on physical activity” were the risk factors for depression and anxiety. The study revealed 73.8 percent of respondents have long-term health-related complications where half (52.8%) of the respondents think that the COVID-19 pandemic has had an effect on their physical health. Conclusions: This study shows that throughout the COVID-19 period, a substantial percentage of Jahangirnagar University students experienced physical and psychological health issues. Proper initiatives should be taken by government and policymakers to boost up the mental and physical health condition of students.